2019
DOI: 10.3390/polym11020317
|View full text |Cite
|
Sign up to set email alerts
|

Dipolar Glass Polymers Containing Polarizable Groups as Dielectric Materials for Energy Storage Applications. A Minireview

Abstract: Materials that have high dielectric constants, high energy densities and minimum dielectric losses are highly desirable for use in capacitor devices. In this sense, polymers and polymer blends have several advantages over inorganic and composite materials, such as their flexibilities, high breakdown strengths, and low dielectric losses. Moreover, the dielectric performance of a polymer depends strongly on its electronic, atomic, dipolar, ionic, and interfacial polarizations. For these reasons, chemical modific… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 15 publications
0
32
0
Order By: Relevance
“…The space charge polarization is characterized by a peak at its glass transition temperature and dipolar polarization is due to the motion of the side group of polymers at low temperatures. 33 The low temperature in PVDF is related to the local motions of the frozen in main chains in the amorphous region of semi-crystalline polymer and the high-temperature peak is associated with molecular motions in amorphous-crystalline boundaries. 34,35 In air-gap TSDC, the charge carriers are not in the position to join with the image charges at the adjoining electrode due to blocking of the electrode by the adjacent air-gap.…”
Section: Resultsmentioning
confidence: 99%
“…The space charge polarization is characterized by a peak at its glass transition temperature and dipolar polarization is due to the motion of the side group of polymers at low temperatures. 33 The low temperature in PVDF is related to the local motions of the frozen in main chains in the amorphous region of semi-crystalline polymer and the high-temperature peak is associated with molecular motions in amorphous-crystalline boundaries. 34,35 In air-gap TSDC, the charge carriers are not in the position to join with the image charges at the adjoining electrode due to blocking of the electrode by the adjacent air-gap.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the dipole moment can be modified by introducing polar single molecules [58], such as -CN, -NO 2 , and -SO 2 -, or polar polymers [59][60][61], including polystyrene, poly(2-hydroxyethyl methacrylate), and poly(dopamine methacrylamide), which allow the rotation of dipoles in the free volume of polymers, thereby leading to an improvement in the dielectric constant. Dipolar polarization has been recently utilized to increase the dielectric Fig.…”
Section: Dipolar Polarization In Ferroelectric Pvdf Derivativesmentioning
confidence: 99%
“…On the other hand, the dipole moment can be modified by introducing polar single molecules [ 58 ], such as –CN, –NO 2 , and –SO 2 –, or polar polymers [ 59 61 ], including polystyrene, poly(2-hydroxyethyl methacrylate), and poly(dopamine methacrylamide), which allow the rotation of dipoles in the free volume of polymers, thereby leading to an improvement in the dielectric constant. Dipolar polarization has been recently utilized to increase the dielectric constant of triboelectric materials by attaching polar groups with large dipole moments to the side chain of polymers [ 22 ]; Lee et al demonstrated that the PVDF-graft copolymer remarkably increased the triboelectric output performance (Fig.…”
Section: Dipolar Polarization In Ferroelectric Pvdf Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…This mechanism stands out over the others by achieving a high polarized state while keeping a relatively low dissipation behavior, since other mechanisms capable of reaching high polarizations (e.g., ionic and interfacial), usually depend on the presence of ionic species, whose diffusion increases the dissipative character of the material, in addition to affecting its much-needed insulating property [1,12,13]. To date, there is a significant number of reports that summarize and explain the physics and chemistry behind this class of materials, allowing to improve their understanding [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%